Implementation of Sustainable Tourism and Performance of Local Tourism Revenue in North Toraja Regency - Ilham Ibrahim; Lukman Hakim; Nuryanti Mustari; Fatmawati (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Tourism is now viewed as a strategic sector that acts as a primary driver of national economic growth. This role is no longer solely the responsibility of the Ministry of Tourism but has become a shared development agenda for all elements of the nation. This study aims to analyze the implementation of the Sustainable Tourism Policy in increasing Regional Origin Revenue in North Toraja Regency. The researcher used qualitative methods, with research data obtained from observations, interviews, documentation, and media reviews. Data validation was carried out through triangulation of sources, techniques, and time, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that sustainable tourism in North Toraja Regency has been effective. The effectiveness of sustainable tourism policy is characterized by active cross-sectoral coordination, progressive participation of policymakers, and support from the community and tourism stakeholders. However, the implementation of this policy also faces challenges, including weak transparency in retribution reporting and miscommunication between the local government and tourist attraction managers, which have resulted in a decline in Regional Original Revenue (PAD) in 2023-2024. Therefore, strengthening coordination, transparency, and communication between stakeholders is crucial to maintaining the sustainability and effectiveness of future policies.